From Digitisation to Full Digital Banking: A Systematic Literature Review on the Multilevel Integration of Industry 4.0 Technologies and Conceptual Frameworks in Banking Transformation - Siti Masitoh; Naila Hali Sylvia (LPPM STIE Kasih Bangsa, 2025)
This study conducts a systematic qualitative literature review to examine the transformation of banking from basic digitisation to full digital banking through the multilevel integration of Industry 4.0 technologies. Synthesising peer-reviewed research across information systems, banking, and innovation studies, the review analyses how technologies such as artificial intelligence, big data analytics, cloud computing, blockchain, and platform architectures reshape banking at the micro (customer), meso (organisational), and macro (industry ecosystem) levels. The findings show that digital banking transformation is a non-linear, socio-technical process in which technological adoption generates value only when complemented by dynamic organisational capabilities, governance mechanisms, and supportive regulatory frameworks. The review further highlights the growing importance of platformisation, open banking, and fintech collaboration in redefining competitive boundaries and value creation in the banking sector. By integrating multilevel perspectives and established conceptual frameworks, this study advances theoretical understanding of digital banking transformation and offers insights for managers and policymakers navigating the transition toward full digital banking.